Local electoral systems in Western Europe - van der Kolk, Henk (2005)
This article describes and discusses the wide range of local electoral systems in Western Europe. It is shown that there are many different local electoral systems used in Western Europe. In many countries these local electoral systems are not the same as the electoral system used in national parliamentary elections. The question is addressed whether local electoral systems matter. Two potential ways to answer this question are explored, but actual research along these lines appears to be very scarce. This means that the debate on the pro's and con's of local electoral systems will probably continue without much guidance from empirical research. It is argued that careful experiments at the local level might give both politicians and political scientists some insight in the consequences of changing the local electoral system.